2020
DOI: 10.1002/jdd.12356
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of optional pairing in clinical dental training

Abstract: Purpose The aim of this study was to investigate the perceived satisfaction of optional pairing in undergraduate clinical dental training of fourth‐ and fifth‐year dental students and newly graduated intern dentists in the subject of conservative dentistry and endodontics. Methods Data were collected through a paper‐based 2‐part questionnaire. The first part was made of 3 questions; gender, undergraduate dental year, and grade point average (GPA). The second part involved 9 questions about assistant student‐ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…In addition, fourth-year students are distributed as partners, and it was shown in a published study that clinical pairing was beneficial in conservative and prosthodontics clinical training and contributed to reducing stress and strain levels. 25 Meanwhile, the stress regarding treating patients for the first time was not significantly present among fifth-year students, who were familiar with treating new patients after a year of practicing, unlike the fourth-year students, who scored a significant stress level regarding this factor. This result was in agreement with a previous study that showed that the patient training factor of the DES scored higher among fourth-year students than fifth-year students.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, fourth-year students are distributed as partners, and it was shown in a published study that clinical pairing was beneficial in conservative and prosthodontics clinical training and contributed to reducing stress and strain levels. 25 Meanwhile, the stress regarding treating patients for the first time was not significantly present among fifth-year students, who were familiar with treating new patients after a year of practicing, unlike the fourth-year students, who scored a significant stress level regarding this factor. This result was in agreement with a previous study that showed that the patient training factor of the DES scored higher among fourth-year students than fifth-year students.…”
Section: Discussionmentioning
confidence: 89%
“…junior third-year students asked to continue to work in pairs with senior students so that they would receive advice and clarifications on issues that were not clarified or taught by instructors, thereby recognising that the transition between simulation and clinical work is difficult (Table 2). The advantages of this pairing system should also be considered for the seniors, as it has been reported that this scheme helps the treatments to take place faster, thereby facilitating a quicker transfer of instruments and materials, improving diagnostics skills and treatment planning, 25 enhancing the learning experience, 26 and adding a level of motivation for learning for both the mentee and the mentor. 27 All student groups asked instructors to provide more frequent, more constructive and better feedback (Table 2).…”
Section: Discussionmentioning
confidence: 99%